Project on Human Development in Chicago Neighborhoods (PHDCN): Gift Wrap, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Gift Wrap instrument. It was administered to subjects in Cohort 0 and was designed to observe the impulsivity and restraint of the subject. A research assistant (RA) was provided with a previously wrapped gift for the subject along with other wrapping supplies. The RA informed the subject that he/she had a gift for the subject but that the gift needed to be wrapped so it would be a surprise. The RA then asked the subject not to look and positioned the subject so that the subject was facing away from the RA. The RA then stood approximately three feet behind the subject and pretended to wrap the gift by crinkling and shaking the wrapping supplies. The RA observed the subject in this manner for 60 seconds and coded the subject's reaction to the gift wrapping noises. After the allotted time, the subject was presented with the gift that had previously been wrapped.